2003
DOI: 10.5326/0390551
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of AntiBabesia Antibodies in Stray Dogs and American Pit Bull Terriers and American Staffordshire Terriers From North Carolina

Abstract: Stray dogs (n=359) and kennel dogs (n=149) from North Carolina were tested for evidence of antiBabesia antibodies. AntiBabesia antibodies were detected in 21/359 and 22/149 of the stray and kennel dogs, respectively. A total of 57 dogs from both groups were tested for babesiasis by light microscopy and polymerase chain reaction (PCR). Babesia deoxyribonucleic acid (DNA) was detected in 3/28 of the stray dogs and 14/29 of the kennel dogs. When Babesia DNA was detected by PCR, the species-specific PCR results di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 17 publications
4
63
0
5
Order By: Relevance
“…In our case‐control study we attempted to provide a more comprehensive clinical picture of infection with B. conradae in dogs including hematologic, biochemical and thorough infectious disease testing. In our study, similar to findings from previous smaller studies, dogs testing positive for B. conradae were more likely to be anemic and had lower median hematocrits than control dogs 1, 7, 18. Reticulocyte counts were not routinely performed as part of the present study, but dogs that tested positive for B. conradae were more likely to have a macrocytic, hypochromic anemia with an increased red cell distribution width, suggestive of a regenerative anemia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our case‐control study we attempted to provide a more comprehensive clinical picture of infection with B. conradae in dogs including hematologic, biochemical and thorough infectious disease testing. In our study, similar to findings from previous smaller studies, dogs testing positive for B. conradae were more likely to be anemic and had lower median hematocrits than control dogs 1, 7, 18. Reticulocyte counts were not routinely performed as part of the present study, but dogs that tested positive for B. conradae were more likely to have a macrocytic, hypochromic anemia with an increased red cell distribution width, suggestive of a regenerative anemia.…”
Section: Discussionsupporting
confidence: 87%
“…Reticulocyte counts were not routinely performed as part of the present study, but dogs that tested positive for B. conradae were more likely to have a macrocytic, hypochromic anemia with an increased red cell distribution width, suggestive of a regenerative anemia. The mechanism for this anemia is likely multifactorial, resulting from increased erythrocyte fragility and intravascular hemolysis because of the presence of an intracellular parasite in addition to immune‐mediated extravascular haemophagocytosis 18. Early experimental studies of B. gibsoni found that dogs become Coombs’ positive and develop splenomegaly as a result of expanded red and white pulp with increased numbers of macrophages, phagocytized erythrocytes or hemosiderin granules along with increased plasma cells with persistent parasitemia 18.…”
Section: Discussionmentioning
confidence: 99%
“…This dog was B. henselae seronegative prior to and after antibiotic therapy. Similar discrepancies between serology and PCR results have been reported in association with other chronic, occult, intracellular canine vector-borne diseases, including babesiosis and leishmaniasis (14,15). Also, this dog, similar to a subset of B. henselae-infected dogs, was R. rickettsii seroreactive, potentially due to concurrent exposure to flea-transmitted Rickettsia felis (13).…”
mentioning
confidence: 51%
“…The recent development of recombinant ELISA assays has improved test specificity (Verdida et al, 2004). Several PCR methods have been reported to diagnose B. gibsoni infection with high sensitivity and specificity (Birkenheuer et al, 2003;Inokuma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%